Implementasi Manajemen Kurikulum untuk Menghasilkan Kesejahteraan Sekolah - Isti Wulandari; Hendro Widodo; Sukirman Sukirman (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2025)
Curriculum management is a strategic component in ensuring educational quality, particularly in the context of vocational education such as Vocational High Schools (SMK). Changes in national education policy and the dynamics of industry demand an adaptive, participatory, and contextual curriculum management system. This study aims to uncover how the implementation of curriculum management at SMK Muhammadiyah 1 Bambanglipuro contributes to improving school well-being, encompassing the dimensions of teachers, students, facilities, and institutions. A qualitative approach with a phenomenological design was used to understand the direct experiences of educational stakeholders related to the curriculum management process at the school. Data were obtained through in-depth interviews, observations, and documentation studies with three main participants: the principal, the vice principal for curriculum, and teachers. The results indicate that the implementation of curriculum management reflects synergy with industry, adjustments to the Independent Curriculum, and ongoing teacher training. Collaborative practices, such as the Teaching Factory with industry partners (Astra, Daihatsu, Jogja TV), also support the achievement of school well-being, both professionally, materially, and institutionally. This study recommends strengthening the curriculum evaluation system and developing industry partnerships as sustainable strategies to improve school quality and well-being.